Antibacterial Activity of Cinnamon Extract (Cinnamomum burmannii) against Staphylococcus aureus and Escherichia coli In Vitro - Nita Parisa; Rahma Nur Islami; Ella Amalia; Mariana Mariana; Riana Sari Puspita Rasyid (HM Publisher, 2019)
Abstract Infectious disease is one of the most common diseases in the world. Staphylococcus aureus and Escherichia coli are two common causes of infection and are resistant to many antibiotics, so the new agents are needed to overcome antibiotic resistance. Cinnamon is often used as a preservative because it has antibacterial activity. Cinnamomum burmannii is kind of native cinnamon from Indonesia. The antimicrobial active compounds cinnamaldehyde and eugenol are the main reasons for its antibacterial activity. This study observed the efficacy of the cinnamon extract (Cinnamomum burmannii) as antibacterial against Staphylococcus aureus and Escherichia coli. An experimental study, in vitro using Post-test Only Control Group Designed, has been done in Microbiology and Biotechnology Laboratory of Medical Faculty of Sriwijaya University. Cinnamon was extracted, then tested for its antibacterial activity using well diffusion and serial dilution to determine diameter of inhibition zone and minimum bactericidal concentration. Phytochemical tests were also conducted to determine the antibacterial compounds of cinnamon extract. Ethanol extract of cinnamon was able to inhibit the growth of Staphylococcus aureus with MBC 5% and inihibitory zone 6,84±0,68 mm and Escherichia coli with MBC 10% and inhibitory zone 5,69±0,69 mm. Cinnamon extract which has the greatest effectiveness is concentration of 40% with inhibition zone 15,69±0,80 mm (Staphylococcus aureus) and 9,63±0,59 mm (Escherichia coli). This ability is due to the antibacterial compounds as evidenced by positive results in various phytochemical tests. Cinnamon extract is effective as antibacterial against Staphylococcus aureus and Escherichia coli in vitro. Keywords: efficacy, antibacterial, Cinnamomum burmannii, Staphylococcus aureus, Escherichia coli